Emergence of invasive Streptococcus dysgalactiae subsp. equisimilis in Spain (2012-2022): genomic insights and clinical correlations - Guillem López de Egea; Aida González-Díaz; Randall J Olsen; Gérard Guédon; Dàmaris Berbel; Immaculada Grau; Jordi Càmara; Lucía Saiz-Escobedo; Sara Calvo-Silveria; Irene Cadenas-Jiménez; José María Marimón; Emilia Cercenado; et al. (International Journal of Infectious Diseases)
Objectives: An increase in Streptococcus dysgalactiae subsp. equisimilis (SDSE) infections has been documented worldwide. This study aims to analyze invasive disease caused by SDSE (iSDSE) in adults over an 11-year period in Spain. Methods: We conducted a retrospective, laboratory-based study of iSDSE detected at Hospital Universitari de Bellvitge (HUB) from 2012 to 2022 (n = 89) and isolates collected in three Spanish hospitals in 2018 (n = 22). Clinical data from HUB were collected. Isolates were tested for antimicrobial susceptibility (European Committee on Antimicrobial Susceptibility Testing 2023), subjected to whole genome sequencing and analyzed for mobile genetic elements (MGEs). A mouse model was used to analyze virulence. Results: iSDSE episodes at HUB occurred predominantly in older patients with comorbidities (particularly, diabetes, chronic heart disease, and malignancies). Whole genome sequencing revealed a high genetic diversity, with the most common lineages being CC15, CC17, and CC20. Various virulence factors, including the superantigen speG, were identified. Macrolides, lincosamides, and tetracyclines exhibited the highest resistance rates (>27%) and changed over time, linked to multiple MGEs. The mouse model highlighted the virulence of the CC20-stG62647 lineage, but these results were discordant with clinical data. Conclusion: iSDSE incidence is increasing and associated with older patients with comorbidities. Genetically, SDSE is diverse with a high capacity to integrate MGEs carrying resistance determinants. Mouse model studies showed the enhanced virulence of the CC20-stG62647 lineage. These findings underscore the need for ongoing surveillance of this emerging pathogen.